Exploring nature-based solutions’ effectiveness indicators for climate change adaptation: a systematic review - Horneman, Fabienne; Torresan, Silvia; Furlan, Elisa; Critto, Andrea (Frontiers in Environmental Science, 2026)
Nature-Based Solutions (NBSs) are increasingly incorporated for climate change adaptation and risk reduction, yet the lack of a standardized evaluation framework and definitions hinder the accurate assessment of their effectiveness. This systematic review, covering articles published between 2008 to 2023 obtained through Scopus, aims to bolster NBS applicability by focusing on effectiveness indicators and evaluation methods used within a wide array of case studies where NBS influence climate adaptation through ecosystem service provisioning. The 27 analyzed key articles include a diverse range of coastal NBSs, including 36 case studies, often implemented at the micro- or meso-scale, each designed to address facets of climate adaptation through the provisioning of ecosystem services such as carbon sequestration (n = 16), erosion reduction (n = 11), flood reduction (n = 16), or improvement of water quality (n = 15). The review revealed a prevalent reliance on process-based performance indicators (51.9%) often applied without accounting for synergies and trade-offs, and/or incorporating impact indicators (70.4%) that assess changes in environmental conditions in order to evaluate NBSs’ effectiveness. Monitoring focused primarily on environmental, hydrological, climatic, and biological performance and impact indicators, while frequently neglecting socio-economic factors. A shift towards a nested, performance-centric approach that incorporates a broader range of socio-economic impact indicators and expands spatio-temporal scales could enhance NBSs adoption. Utilizing advanced data techniques and modelling indicators can further strengthen the evidence base and facilitate the adoption of NBSs for climate adaptation.